Displacement of a Functional Femoral Pseudoarthrosis in a Dog - Jevens, D. J.; Flo, Gretchen L.; Stickle, R. L. (Veterinary and Comparative Orthopaedics and Traumatology, 1992)
A mature mixed breed dog was evaluated for acute onset of non-weight-bearing lameness involving the right hind limb. The dog had, reportedly, walked normally for the previous three years. A diagnosis of acute displacement of a functional femoral pseudoarthrosis was made. The pseudoarthrosis was stabilized using a dynamic compression bone plate and an autogenous cancellous bone graft. The dog was walking normally five months after the operation.
Keywords: Canine; femur; functional pseudoarthrosis